Literature, education and Republic. André Maurois and the instinct of bourgeois happiness (Second part) - de la Arada Acebes, Raquel; Garcia Farrero, Jordi; Vilanou Torrano, Conrad (Historia y Memoria de la Educación, 2017)
This article describes the relationship between literature and the educational ideals of André Maurois (1885-1967). First the paper reviews his formative years in the shadow of the philosopher Alain, who was his teacher at Rouen Lyceum. It also highlights the presence of military elements in his educational universe to the extent that the educational workenfoques of the Third French Republic (1870-1940) is understood in the light of the combination of intelligence and weapons, that is, between the lyceum and the garrison. Maurois traveled throughout the United States. He was concerned about the atmosphere of crisis in the decade of the twenties and thirties, and took his inspiration from Marshal Hubert Lyautey in order to determine the characteristics of the art of leadership that, along with the art of thinking, the art of loving, the art of working, and the art of growing old, give shape to the various aspects of his work Art of Living (1939). In fact, Art of Living follows in the best of French pedagogical traditions (Montaigne, Rousseau, Alain) and highlights the importance of the task of living. Ultimately, and from the bourgeois stance as a lover of order, Maurois wished for the human being to lead a happy life, in keeping with the Republican values inherited from 1789 Revolution. In short, Maurois was an intellectual who combined tradition and modernity in a changing world that, after World War I (1914-1918), left behind the false securities of the Belle Époque, without forgetting the perspective of human happiness beyond any metaphysical consideration. As this paper endeavors to show, his work had a great impact in Spain, before and after the Civil War, and contributed decisively in changing the public moral of our country.